Changes in Running Kinematics and Kinetics Following a 10 km Run - Mark Reinking; Emily Hill; Kathryn Marr; Kasey Melness; Dominique Ortiz; Elsa Racasan; Nicholas Wedl; Joshua White; Brian Baum (International Journal of Sports Physical Therapy)
# Background